Autophagy in spinal muscular atrophy: from pathogenic mechanisms to therapeutic approaches - Rashid, Saman; Dimitriadi, Maria (Frontiers in Cellular Neuroscience, 2024)
Spinal muscular atrophy (SMA) is a devastating neuromuscular disorder caused by the depletion of the ubiquitously expressed survival motor neuron (SMN) protein. While the genetic cause of SMA has been well documented, the exact mechanism(s) by which SMN depletion results in disease progression remain elusive. A wide body of evidence has highlighted the involvement and dysregulation of autophagy in SMA. Autophagy is a highly conserved lysosomal degradation process which is necessary for cellular homeostasis; defects in the autophagic machinery have been linked with a wide range of neurodegenerative disorders, including amyotrophic lateral sclerosis, Alzheimer’s disease and Parkinson’s disease. The pathway is particularly known to prevent neurodegeneration and has been suggested to act as a neuroprotective factor, thus presenting an attractive target for novel therapies for SMA patients. In this review, (a) we provide for the first time a comprehensive summary of the perturbations in the autophagic networks that characterize SMA development, (b) highlight the autophagic regulators which may play a key role in SMA pathogenesis and (c) propose decreased autophagic flux as the causative agent underlying the autophagic dysregulation observed in these patients.